Thrombotic Status Analyser - Gorog, Diana A; Kovacs, Iren B (Thrombosis and Haemostasis, 1995)
A physiologically relevant global in vitro test is described which allows the overall assessment of both thrombotic and thrombolytic activities of blood. In principle, native blood is drawn in pulses through a capillary tube where haemodynamic forces induce a platelet reaction culminating in vessel occlusion. Dislodgement/disintegration of the stabilised thrombus under pressure is a reflection of thrombolysis. Evidence is presented for the platelet-rich nature of the occlusion and that disruption of the thrombus and re-established patency is the result of thrombolysis, that is fibrinolysis with significant contribution from platelets.This test sensitively detects hypercoagulability (stasis); platelet hyperreactivity (coronary artery disease); anti-platelet effect (aspirin, prostacyclin) and the thrombolytic effect of, thrombin generation by, and resistance to streptokinase. Therefore, this overall assessment of thrombotic status could be of great diagnostic and therapeutic benefit in clinical practice.